Calibration System for Zener Voltage Standards Using a 10 V Programmable Josephson Voltage Standard at NMIJ - Maruyama, Michitaka; Iwasa, Akio; Yamamori, Hirotake; Shih-Fang Chen; Urano, Chiharu; Kaneko, Nobu-hisa (IEEE transactions on instrumentation and measurement, 2015)
We have developed a calibration system for the Zener voltage standards using a programmable Josephson voltage standard (PJVS) for liquid-helium consumption reduction and improvement in the calibration performance. The PJVS array is composed of 524288 niobium nitride (NbN)-based overdamped Josephson junctions and is cooled by a 10-K compact cooler. To verify the validity of the system, indirect and direct comparisons of the PJVS system and our conventional Josephson voltage standard system have been carried out. As a result, an agreement within a relative expanded uncertainty of 8.4 × 10 -10 was obtained for a nominal voltage of 10 V. We also discuss the uncertainty sources in the calibration of the Zener voltage standards using our PJVS system.